(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The Patient’s Denture Assessment (PDA) questionnaire, developed in Japan, aims to evaluate patients’ satisfaction with their dentures and support the improvement of treatment outcomes. This study presents the cultural adaptation process and initial validation of the Vietnamese version of the PDA (PDA-V). Objectives and Methods: The adaptation process included initial translation, synthesis of translations, back-translation, expert panel review, and preliminary testing of the translated version. The pre-final version was validated with 40 participants at Ho Chi Minh City Dental Hospital. Patients self-assessed their dentures using a Visual Analog Scale (VAS). Results: Among the 40 participants, 29 completed the questionnaire a second time after 10-14 days. Reliability was assessed through Cronbach’s alpha and test-retest coefficients to evaluate stability over time. The PDA-V demonstrated good reliability and content validity after preliminary testing. Conclusion: The Vietnamese version of the PDA underwent rigorous cultural adaptation, ensuring reliability and validity, and is suitable for future research in Vietnam.